O efeito de um programa de exercício físico multicomponente em idosos com doença de Alzheimer - Flávia Alexandra Borges Machado (2017)
Dementia, particularly Alzheimer's Disease (AD), is one of the major causes of impairment and dependence of elderly in the world. This syndrome is associated with progressive cognitive decline, along with functional impairment, and adversely affects physical conditioning. The aim of this study was to assess the effectiveness of a multicomponent training (MT) on physical fitness, ability to perform activities of daily living (ADL), and cognitive function in people with AD. A controlled trial of 10 community-dwelling individuals diagnosed with mild to moderate AD were divided into two groups (control - CG or intervention -IG) according to their aim and availability to voluntarily participate in this study. AD subjects and their caregivers were submitted to a 3-month MT (50-60 minutes/session), including aerobics, muscle strengthening, flexibility, balance and postural exercise. Complimentarily, and whenever possible, cognitive stimulation was promoted, enabling the interaction patient-caregiver. Before and after intervention, the following tests were used: Senior Fitness Test, Alzheimer Disease Assessment Scale - Cognitive, Trail Making Test and Disability Assessment for Dementia Scale. Results from a repeated measures ANOVA revealed a significant time effect on muscle strength (F=13, p<0.05) in upper and lower body, and in the ability to perform ADL (group and interaction factors, p<0.05). Additionally, in the IG, there was a significantly better performance on cardiorespiratory fitness (p<0.05). The CG's cognitive performance decreased over time. Data suggests that a bi-weekly MT may be an important non-pharmacological intervention to mitigate the physical, functional and cognitive decline of older community residents with AD.